Hematopathological alterations of major tumor suppressor cascade, vital cell cycle inhibitors and hematopoietic niche components in experimental myelodysplasia. (1st August 2017) - Chatterjee, Ritam; Gupta, Shubhangi; Law, Sujata
Abstract: Myelodysplastic syndrome (MDS) is a poorly understood dreadful hematopoietic disorder that involves maturational defect and abnormalities in blood cell production leading to dysplastic changes and peripheral blood pancytopenia. The present work aims in establishing the mechanistic relationship of the expressional alterations of major tumor suppressor cascade, vital cell cycle inhibitors and hematopoietic microenvironmental components with the disease pathophysiologies. The study involves the development of N-N′ Ethylnitrosourea (ENU) induced mouse model of MDS, characterization of the disease with blood film and bone marrow smear studies, scanning electron microscopic observation, mitochondrial membrane potential determination, flowcytometric analysis of osteoblastic and vascular niche components along with the expressional study of cleaved caspase-3, PCNA, Chk-2, p53, Ndn, Gfi-1, Tie-2, Sdf-1, Gsk-3β, p18 and Myt-1 in the bone marrow compartment. Dysplastic features were found in peripheral blood of MDS mice which seemed to be the consequence of three marrow pathophysiological conditions viz; aberrant rise of cellular proliferation, increased apoptosis and crowding of abnormal blast population. Expressional decline of the p53 cascade involving Chk-2, p53, Ndn, Gfi-1 along with the downregulation of major cell cycle inhibitors seemed to be associated with the hyper-proliferative nature of bone marrow cells during MDS. Moreover the disruption of osteoblastic niche components added to the decreased hematopoietic quiescency. Increased marrow vascular niche components signified the pre-malignant state of MDS. Elevated cellular apoptosis and rise in the blast burden were also found to be associated with the p53 expression dependent collapsing of mitochondrial membrane potential and upregulation of Tie-2 respectively. The study established the mechanistic correlation between the alterations of the mentioned signaling components and hematopoietic anomalies during MDS which may be beneficial for the development of therapeutic strategies for the disease. Graphical abstract: Highlights: Cellular hyper-proliferation in MDS marrow associated with p53 axis deregulation. Aberrant cell division and decline of vital cell cycle inhibitors in MDS marrow. p53 axis alteration related mitochondrial disruption and apoptosis in MDS marrow. p53 decline, Tie-2 up-regulation and associated blast burden rise in MDS marrow. MDS pathophysiologies associated with alteration of hematopoietic niche components.